The Cauchy Problem for the Incompressible 2D-MHD with Power Law-Type Nonlinear Viscous Fluid - Jae-Myoung Kim (Advances in Mathematical Physics)
We investigate a motion of the incompressible 2D-MHD with power law-type nonlinear viscous fluid. In this paper, we establish the global existence and uniqueness of a weak solution u,b depending on a number q in ℝ2. Moreover, the energy norm of the weak solutions to the fluid flows has decay rate 1+t−1/2.